2015
DOI: 10.1126/science.1262118
|View full text |Cite
|
Sign up to set email alerts
|

Tilt engineering of spontaneous polarization and magnetization above 300 K in a bulk layered perovskite

Abstract: Crystalline materials that combine electrical polarization and magnetization could be advantageous in applications such as information storage, but these properties are usually considered to have incompatible chemical bonding and electronic requirements. Recent theoretical work on perovskite materials suggested a route for combining both properties. We used crystal chemistry to engineer specific atomic displacements in a layered perovskite, (Ca(y)Sr(1- y))(1.15)Tb(1.85)Fe2O7, that change its symmetry and simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
180
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(188 citation statements)
references
References 40 publications
(1 reference statement)
5
180
1
2
Order By: Relevance
“…Due to their unusual lattice couplings and dynamics, there has been renewed recent interest in tuning the properties of layered materials based on the perovskite structure, including proper, 1,2 and improper, [3][4][5] ferroelectricity, the electrocaloric effect, 6 and colossal magnetoresistance. 7 Unprecedented control of ferroelectricity in layered perovskites has been achieved, for example, by engineering non-polar lattice instabilities that can combine in the ground state to produce a net polarisation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their unusual lattice couplings and dynamics, there has been renewed recent interest in tuning the properties of layered materials based on the perovskite structure, including proper, 1,2 and improper, [3][4][5] ferroelectricity, the electrocaloric effect, 6 and colossal magnetoresistance. 7 Unprecedented control of ferroelectricity in layered perovskites has been achieved, for example, by engineering non-polar lattice instabilities that can combine in the ground state to produce a net polarisation.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a large amount of renewed interest in improper ferroelectric mechanisms recently, particularly in studying the coupling between two nonpolar zone-boundary lattice modes with octahedral tilt character in the RuddlesdenPopper layered perovskites, which has been discussed in the context of "hybrid improper ferroelectricity" [2,[35][36][37]. Here we reveal a mechanism by which two zone-boundary modes, implicitly dependent on orbital degrees of freedom, combine to give polar zone-centered displacements.…”
Section: Charge Ordering and Improper Ferroelectric Couplingmentioning
confidence: 99%
“…Unfortunately, the measurements of pyrocurrent or polarization-electric field (PE) loops in the P nn2 phase at higher temperatures above the magnetic ordering transition has been impossible due to leakage currents at these higher temperatures. Obtaining such direct measures of the switchable nature of the crystallographically identified polar ground state is a substantial future challenge for this and other recently reported hybrid improper ferroelectrics [2,35]. Our following discussion on ferroelectric switching pathways is based on symmetry arguments alone.…”
Section: Charge Ordering and Improper Ferroelectric Couplingmentioning
confidence: 99%
“…al. [24] on polar double perovskite (Ca y Sr 1−y ) 1.15 Tb 1.85 Fe 2 O 7 has shown that the polarization and magnetization in this material co-exist at room temperature and that the polarization is induced through a hybrid improper mechanism. Hence, it appears that HIF may be a promising and practical means to design new magnetoelectrics (MEs).…”
Section: Introductionmentioning
confidence: 99%